Investigation of the failure intensity indicator in Lublin water supply pipelines - Kowalski, Dariusz; Kowalska, Beata; Kuzioła, Elżbieta (Instal, 2019)
The paper presents the results of the study of the failure intensity indicator in Lublin water supply pipelines. The research was based on the local water company database containing a list of failures in the 1997-2017 period. The main lines, distribution conduits and house connections pipes were analyzed. As a result, the downward trend in the failure intensity indicator of all analyzed types of pipes were detected. Similarly the purposefulness of modernization activities conducted by the water company was indicated. The obtained values of the failure intensity indicator are significantly lower than the average values in Poland in relation to main lines and conduits and slightly higher in the case of house connections. Assuming average times of network pipes troubleshooting, the probability of correct work of analyzed network pipes were estimated. The article also includes the failure rate that intuitively interprets the probability of correct work values.